The Intertwining of Educational Dualism in post-New Order Indonesia - Suzanna Eddyono (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2018)
This study focuses on continuities and changes in the dualism of national education after the collapse of the New-Order Regime in 1998. It argues that the Indonesian dualism of education may serve as a significant context in shaping the existing tensions in citizenship education in post- New-Order Indonesia. Drawing from a thematic analysis of citizenship education documents, related policy, and interviews with authors and higher education teaching staff, this study echoes the latest observations that reveal a more intertwining than rigid separation of the continuing dualism of national education. Yet, unlike the previous studies that reveal the tensions in more Islamic-based education, in its response to a more secular and modern demand, this study further highlights the intertwining of the dualism of education palpable in the citizenship education policy in post-New-Order Indonesia. It further calls for policy makers and educators to evaluate the existing citizenship education curriculum and its implementation within the context of an intertwined educational dualism in Indonesia. As such, this paper further aims to highlight the urgency of considering broader cultural and political contexts and actors involved in the process of reproducing official narratives of Indonesianess in the national curricula.